Enhancement of Hybrid SPEEK Based Polymer–Cyclodextrin-Silica Inorganic Membrane for Direct Methanol Fuel Cell Application - Kusworo, Tutuk Djoko; Hakim, Muhammad Fahmi; Hadiyanto, H (International Journal of Renewable Energy Development, 2017)
Direct methanol fuel cell (DMFC) is one of several types of fuel cells that use proton exchange membrane (PEM) as a liaison between the reaction at the cathode and anode. Polyether-ether ketone (PEEK) is one of the aromatic polymer that can be applied in DMFC because of its characteristics that are resistant to DMFC environment. The polymer is also quite easy in the sulfonation process using concentrated sulfuric acid. However the role of polyether-ether ketone as DMFC membrane material is still lack of advantage due to its low conductivity and therefore the modification is required to increase the value of proton conductivity of the membrane. The purpose of this experiment is to modify the membrane (sPEEK) with the addition of cyclodextrins-silica, additive variation charge of 2%, 6% and 10%, time and temperature were fixed at 4 hours and 65oC. The results showed the best results of membrane sPEEK was obtained at the addition of -cyclodextrin -silica 10% with the membrane characteristics of ion exchange capacity of 2.19 meq / g polymer, the degree of sulfonation of 81%, methanol permeability of 3.09 x 10-9 cm2 / s and water uptake membrane of 64%.Article History: Received January 18th 2017; Received in revised form April 21st 2017; Accepted June 22nd 2017; Available onlineHow to Cite This Article: Kusworo, T.D., Hakim, M.F. and Hadiyanto, H. (2017) Enhancement of Hybrid SPEEK Based Polymer–Cyclodextrin-Silica Inorganic Membrane for Direct Methanol Fuel Cell Application. International Journal of Renewable Energy Development, 6(2), 165-170.https://doi.org/10.14710/ijred.6.2.165-170